Profiles of serum amino acids to screen for catabolic and inflammation status in calves with Mycoplasma bronchopneumonia - TSUKANO, Kenji (J Vet Med Sci, 2014)
The aim of the present study was to investigate the relationships between serum amino acid profiles in normal and calves with Mycoplasma bronchopneumonia. Serum free amino acid concentrations in serum obtained from 34 calves with or without Mycoplasma bronchopneumonia were determined by high-performance liquid chromatography. The calves with Mycoplasma were characterized by significantly lower total amino acid and total essential amino acid concentrations and molar ratios of branched-chain amino acid (BCAA) to aromatic amino acid (BCAA/AAA) and BCAA to tyrosine (BTR), and by a significantly higher molar ratio of serine phosphorylation (SPR). The proposed diagnostic cutoffs for BCAA/AAA, BTR and SPR in serum based on ROC analysis for detection of catabolic states associated with Mycoplasma bronchopneumonia were set at <1.75, <2.86 and >0.85, respectively. Our results suggest that determining the profiles of amino acids, especially BTR and SPR, could provide useful diagnostic information in terms of predicting protein catabolism in Mycoplasma bronchopneumonia.